2010
DOI: 10.1590/s0101-32892010000400016
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do desempenho isocinético da musculatura extensora e flexora do joelho de atletas de futsal em membro dominante e não dominante

Abstract: RESUmOObjetivo: avaliar o desempenho isocinético da musculatura extensora e flexora do joelho em atletas de futsal nos membros DO e ND. Metodologia: participaram 23 atletas, com idade de 27,1 ± 3,6 anos, massa corporal 72,7 ± 12,6kg e estatura 1,75 ± 6,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 14 publications
1
8
2
15
Order By: Relevance
“…Compared to other sports at angular speed of 180°/s, a few studies have shown average scores of the extensors lower than those of this study, similarly to the studies which analyzed futsal players (Ferreira et al, 2010), and soccer (Zakas, 2006;Fousekis et al, 2010;Silva et al, 2015), whilst other studies analyzing soccer players showed higher average scores (Da Fonseca et al, 2007;Daneshjoo et al, 2013). In the analysis of the knee flexors, studies with futsal players (Ferreira et al, 2010) and soccer (Zakas et al, 2006;Fousekis et al, 2010;Daneshjoo et al, 2013;Silva et al, 2015) also showed lower average scores whilst other studies showed average scores higher than the athletes of this study (soccer (Da Fonseca et al, 2007), rugby (Larrat et al, 2007) and handball (González-Ravé et al, 2014). At angular speed of 240º/s, all fields of sport analyzed (soccer (Zakas, 2006), rugby (González-Ravé et al, 2014), basketball (Schiltz et al, 2009) and volleyball (Shu & Zhou, 2011)), resulted in average scores higher than in this study, for both knee extensors and flexors.…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinísupporting
confidence: 78%
See 2 more Smart Citations
“…Compared to other sports at angular speed of 180°/s, a few studies have shown average scores of the extensors lower than those of this study, similarly to the studies which analyzed futsal players (Ferreira et al, 2010), and soccer (Zakas, 2006;Fousekis et al, 2010;Silva et al, 2015), whilst other studies analyzing soccer players showed higher average scores (Da Fonseca et al, 2007;Daneshjoo et al, 2013). In the analysis of the knee flexors, studies with futsal players (Ferreira et al, 2010) and soccer (Zakas et al, 2006;Fousekis et al, 2010;Daneshjoo et al, 2013;Silva et al, 2015) also showed lower average scores whilst other studies showed average scores higher than the athletes of this study (soccer (Da Fonseca et al, 2007), rugby (Larrat et al, 2007) and handball (González-Ravé et al, 2014). At angular speed of 240º/s, all fields of sport analyzed (soccer (Zakas, 2006), rugby (González-Ravé et al, 2014), basketball (Schiltz et al, 2009) and volleyball (Shu & Zhou, 2011)), resulted in average scores higher than in this study, for both knee extensors and flexors.…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinísupporting
confidence: 78%
“…However, two studies which analyzed professional soccer players showed higher average scores of flexors than the scores of the athletes of this study (Zabka et al, 2011;Daneshjoo et al, 2013). Compared to other sports at angular speed of 180°/s, a few studies have shown average scores of the extensors lower than those of this study, similarly to the studies which analyzed futsal players (Ferreira et al, 2010), and soccer (Zakas, 2006;Fousekis et al, 2010;Silva et al, 2015), whilst other studies analyzing soccer players showed higher average scores (Da Fonseca et al, 2007;Daneshjoo et al, 2013). In the analysis of the knee flexors, studies with futsal players (Ferreira et al, 2010) and soccer (Zakas et al, 2006;Fousekis et al, 2010;Daneshjoo et al, 2013;Silva et al, 2015) also showed lower average scores whilst other studies showed average scores higher than the athletes of this study (soccer (Da Fonseca et al, 2007), rugby (Larrat et al, 2007) and handball (González-Ravé et al, 2014).…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinícontrasting
confidence: 50%
See 1 more Smart Citation
“…It is noteworthy that in this study, there was no muscular imbalance greater than 10% between the dominant and non-dominant limbs both in IG and CG, in both evaluated moments (pre-and post-test), indicating that the athletes in this study did not present this risk factor for injuries, since this indicative occurs when there are asymmetries higher than 10% between limbs 25 . However, athletes from both groups, both in the dominant and non-dominant limbs, presented flexors/extensors ratio below 50% before intervention, indicating muscle imbalance in the knee joint 26 , a factor that predisposes athletes to injuries in this joint.…”
Section: Discussionmentioning
confidence: 47%
“…O desempenho dos atletas em quadra pode estar relacionado diretamente com o nível de preparo da musculatura exigida para a prática do futsal. O quadríceps e os isquiotibiais são os músculos mais exigidos no futsal, pois, destacam-se entre a musculatura mais trabalhada nos tiros curtos, médios e longos, paradas bruscas, chutes, disputas de bolas, saltos e as divididas 8 . Os músculos gastrocnêmios (medial e lateral) auxiliam na flexão plantar da articulação do tornozelo enquanto, A amostra foi constituída por dez acadêmicos praticantes de futsal, com faixa etária de vinte a trinta anos, do sexo masculino, oriundos dos cursos de Engenharias da UNESC.…”
Section: Introductionunclassified